The Neuromuscular Junction: Aging at the Crossroad between Nerves and Muscle - Gonzalez-Freire, Marta; de Cabo, Rafael; Studenski, Stephanie A.; Ferrucci, Luigi (Frontiers in Aging Neuroscience, 2014)
Aging is associated with a progressive loss of muscle mass and strength and a decline in neurophysiological functions. Age-related neuromuscular junction (NMJ) plays a key role in musculoskeletal impairment that occurs with aging. However, whether changes in the NMJ precede or follow the decline of muscle mass and strength remains unresolved. Many factors such as mitochondrial dysfunction, oxidative stress, inflammation, changes in the innervation of muscle fibers and mechanical properties of the motor units probably perform an important role in NMJ degeneration and muscle mass and strength decline in late life. This review addresses the primary events that might lead to NMJ dysfunction with aging, including studies on biomarkers, signaling pathways and animal models. Interventions such as caloric restriction (CR) and exercise may positively affect the NMJ through this mechanism and attenuate the age-related progressive impairment in motor function.